Does Disclosure of Environmental Investment Amounts Affect Debt Financing Costs? Evidence from China's Electric and Heat Power Production and Supply Industry - Cui, Tongwei (Transactions on Economics, Business and Management Research, 2026)
This study examines whether environmental investment disclosure affects corporate debt financing costs. Using manually collected data from 79 A-share listed firms, we find no significant association in OLS regression with robust standard errors. Firm size, leverage, and profitability dominate financing costs. Drawing on information asymmetry and signaling theories, we interpret these findings within China's policy-driven disclosure regime, where disclosure may be viewed as regulatory compliance rather than voluntary commitment, weakening its financial impact.
Keywords: Environmental investment disclosure; debt financing costs; electric and heat power industry; information asymmetry; signaling theory; policy-driven disclosure; China